Saving awareness among UiTM Dungun students / Nurin Ayuni Mahamad Fazil - Mahamad Fazil, Nurin Ayuni (2022)
The introduction of money saving is critical for everyone, particularly the younger generation. They should be provided with information or disclosure about savings to ensure that they are aware of it. Many of their advantages as students stem from the fact that money savings do not only refer to savings at home, but also to savings in banks and other types of savings. As a result, there is a need to comprehend financial literacy and identify the factors that influence students to save money. The study's goal was to assess the level of money-saving awareness, identify the factors that contribute to money-saving awareness, and identify the factors that influence students' money-saving awareness. This study focused on students of all faculties at UiTM Dungun. Based on the findings of this study, the level of saving awareness of UiTM Dungun students was high. Financial knowledge, behaviour and attitude give influence in saving awareness for students. Next, we were able to identify the part in which students are lacking and recommend some management implications for improving student saving awareness. As a result, they are less likely to incur significant debt in the future.